2021
DOI: 10.1021/acsapm.1c00384
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reinforcement via 1D Nanostructure Formation during Melt Blending of Thermoplastics and Thermoplastic Elastomers with Nanophase-Separated UHMWPE/HDPE Wax Reactor Blends

Abstract: Adding inorganic fillers like glass or carbon fibers is common practice for reinforcing engineering thermoplastics to expand their range of applications in lightweight construction. Albeit the advantages of traditional polymer composites are obvious, the quest for sustainable development and a circular economy is driving the development of recyclable all-polymer composites with a low carbon footprint. Melt blending of commodity high-density polyethylene (HDPE) with reactor blends (RB) comprising nanophase-sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Injection molding generally results in better fiber alignment and matrix orientation, thus leading to higher mechanical properties compared to compression-molded samples. 46 While the systems differ, these results are consistent with those reported in the literature. 47 It was demonstrated that with proper mixing to prevent fiber breakage and molding conditions to maintain fiber alignment, PALF could provide a higher reinforcement efficiency than aramid fiber in rubber composite systems.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Injection molding generally results in better fiber alignment and matrix orientation, thus leading to higher mechanical properties compared to compression-molded samples. 46 While the systems differ, these results are consistent with those reported in the literature. 47 It was demonstrated that with proper mixing to prevent fiber breakage and molding conditions to maintain fiber alignment, PALF could provide a higher reinforcement efficiency than aramid fiber in rubber composite systems.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, the percentage increment in the mechanical properties, particularly the modulus obtained, was comparable to that of the injection-molded samples, as observed in ramie, PALF/chopstick, and wood composites. Injection molding generally results in better fiber alignment and matrix orientation, thus leading to higher mechanical properties compared to compression-molded samples . While the systems differ, these results are consistent with those reported in the literature .…”
Section: Resultssupporting
confidence: 88%
“…On the basis of the original data, the Lorentz corrected SAXS curves ( Iq 2 ~ q ) were evaluated. The long period ( L ) could be calculated via the Bragg equation as follow 18 : Lgoodbreak=2πqmax where L is the long period, q max corresponds to the q value of the Lorentz corrected scattering peak.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the original data, the Lorentz corrected SAXS curves (Iq 2 $ q) were evaluated. The long period (L) could be calculated via the Bragg equation as follow 18 :…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%